Purwarupa Sistem Otomasi Perawatan Tanaman Cabai Pada Smart Greenbox Berbasis Iot - Ikram Andika Ukar; Nyoman Karna; I Putu Yowan Nugraha Suparta (Circuit: Jurnal Ilmiah Pendidikan Teknik Elektro, 2022)
Recently, urban communities are interesting gardening as their hobby which can be done at home on narrow land. However, this hobby is faced with several problems, which most of them are workers and busy thus they could not care, monitor and control their plants. The presence of Internet of Things (IoT) technology is a major breakthrough for the problems that exist in society. With IoT, it is easier for people to remotely monitor and control their gardens anytime and anywhere. However, this study develops a prototype of an IoT-based plant watering automation system for chili plants in Greenbox. The design of the prototype is a Cartesian robot with X and Y axes. The prototype performs automatically success depending on the input value of soil moisture or soil pH from the sensor. The result of this research showed that the robot is success automatically watering or giving liquid fertilizer to the Smart Greenbox. The automation carried out by this robot of watering or cultivating based on input from the sensor results. The accuracy obtained from the prototype reached 95.53% for the X axis and 99.15% for the Y axis. The application of this prototype automation system was considered efficient in the using. Finally, the quality of the received data transmission shows good results.